Clinical efficacy of sequential therapy for nodular cystic acne - Xiaolin BU; Lingling ZHANG; Siyuan WU; Wenqi ZHAO (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To assess the clinical efficacy and safety of sequential therapy for nodular cystic acne. Methods Forty three patients with nodular cystic acne were divided into sequential and control groups. In the sequential group, 22 patients were treated with ALA-PDT every two weeks for 3 times, and oral antibiotics in the first stage, followed by chemical peeling once every two weeks for 3 times, and oral isotretinoin in the second stage. Finally, oral isotretinoin alone was given in the last stage. While 21 patients in the control group were treated with isotretinoin alone. The treatments lasted for 16 weeks. After each treatment course, the efficacy and adverse effect were compared between the two therapies. The patients in both groups were followed up for 6 months, and the relapse rate and adverse reactions were recorded. Results In the first stage of treatment, effective rates after the second and the third treatment course were 9.09% and 22.73%, respectively, in the sequential group, and 0 and 4.76%, respectively, in the controls. In the second stage, the effective rates after each treatment course were higher in sequential groups than in the controls (1st treatment course: 50.00% vs. 23.81%; 2nd treatment course: 90.90% vs. 42.86%, and the 3rd treatment course: 100% vs. 66.67%. P<0.05 for 2rd and 3rd treatment). After the third stage of treatment, the effective rate in the sequential and control groups were 100% and 85.71%, respectively (P<0.05). The rates of no relapse and marked improvement were significantly higher in the sequential group than in the controls (100% vs. 73.33%, P<0.05). Conclusion Sequential therapy is effective and safe for nodular cystic acne, with fewer adverse reactions and lower relapse rate.